Correlation Analysis of Anti-Cardiolipin Antibody/D Dimer/C-Reactive Protein and Coronary Artery Lesions/Multiple-Organ Damage in Children With Kawasaki Disease - Xu, Yun-ming; Chu, Yan-qiu; Wang, Hong (Frontiers in Pediatrics, 2021)
The Anticardiolipin antibodies (ACA) are the cardiolipin antibodies. our research showed taht it was correlated with coronary artery lesions (CAL) in children with kawasaki disease. some researchers reported CRP/D Dimer also correlated with CAL in children with KD, but our results showed CRP/D Dimer only correlated with multiple otgans damage (MOD) and not with CAL.